New Imidazole Compounds Derived from Pyrrolidonic and Piperidonic Acids as Non- Steroidic Aromatase Inhibitors - Tabcheh, Mohamad; Baroudi, Moomen; Elomar, Fawaz; Elzant, Amer; Elkhatib, Mazen; Rolland, Valeric (Asian Journal of Chemistry, 2010)
Imidazole and indole compounds derived from pyrrolidine and piperidine carboxylic acids are synthesized and characterized. The inhibition activity of those compounds was evaluated in-vitro on aromatase extracted from human placenta, compared to the first representative non-steroid agent (aminoglutethimide). Imidazoles derivatives showed significant inhibition of aromatase (Ki < 78.0 mM).